War Art
Nedžad Begović’s exhibition entitled “War Art” was created by collecting various materials that have lost their primary function due to war operations. All exhibits are the result of the destruction of Sarajevo and have a story of their own. The author recognizes shapes in the destroyed objects and presents them as ‘arte facts,’ transforming the negative energy of crime into the positive vibrations of human spirituality.